Supply chain transparency through blockchain-based traceability: An overview with demonstration. (December 2020) - Sunny, Justin; Undralla, Naveen; Madhusudanan Pillai, V.
Highlights: Blockchain-based traceability solutions bring better transparency in supply chain. Literature on blockchain-based traceability solutions are mostly conceptual. Blockchain cannot supersede the existing technologies, but can complement them. Smart contracts make blockchain traceability solutions more effective. Blockchain based traceability systems are not free from shortcomings. Abstract: Traceability can be referred to as the ability to track and trace information. Application of traceability can create transparency in supply chains. Conventionally available, centralized traceability solutions are not preferable for supply chains as they are exposed to many problems such as data manipulations, single point of failure, etc. Blockchain, the recently emerged distributed ledger technology, is gaining popularity with its tremendous applications in various fields, particularly in supply chain management. Technically, blockchain is a decentralized and distributed database where information can be securely recorded. Blockchain-based traceability solutions can tackle the shortcomings of centralized traceability solutions. Firms have already started incorporating blockchain into their supply chain activities in order to improve the transparency through tracking and tracing the events. This paper ultimately aims to present an overview of the various blockchain-based traceability solutions reported in the literature. Primarily, this work provides an insight on the possibilities of blockchain traceability solutions in making a supply chain transparent. Apart from this, it analyses how blockchain traceability solutions affect the visibility of various supply chain distribution network designs, and gives an outline on how technologies such as the Internet of Things (IoT), and smart contracts elevate the opportunities of blockchain. In order to demonstrate how blockchain traceability solutions improve supply chain transparency, a Proof of Concept (PoC) for a cold chain scenario is presented using Microsoft Azure Blockchain Workbench.